A review of the recent advances in superhydrophobic surfaces and the emerging energy-related applications. (15th March 2015) - Zhang, P.; Lv, F.Y.
Abstract: A new kind of functional surfaces with particular characteristics, i.e., superhydrophobic surfaces, has recently been developed and applied in many fields, such as airplane, wind turbine, electric power line, photovoltaic cell, heat exchanges, ice slurry generator, and so on. The freezing delay and ice-accumulation avoiding on the surfaces are important to keep stable working condition for these devices. The frictional pressure loss of flow through the tubes or channels with superhydrophobic surfaces is much smaller than that through those without superhydrophobic surfaces. Both the boiling and condensation heat transfer performances on superhydrophobic surfaces can be enhanced. The superhydrophobic surfaces have potential applications and are worthy further investigations. We provide here a review of the fabrications, characterization and the emerging energy-related applications of superhydrophobic surfaces on the basis of the recent progresses of the research and development in this field. The fabrication of superhydrophobic surface, in particular a recently developed SLIPS (slippery liquid-infused porous surface), is summarized. The focuses are placed on the particular characteristics of superhydrophobic surfaces and their applications in energy-related fields. The further research topics are also clarified to promote the future applications. Highlights: Recent progress on superhydrophobic surfaces is reviewed. The superhydrophobic surfaces are gradually used in the energy-related applications. Application of superhydrophobic surfaces can enhance the system performance. The further research topics are proposed.